Analyzing factors that affect e-syariah adoption by shar'ie lawyers - Ramly, Norlida; Said, Mohd Fuaad; Choo, Wei Chong; Ab Rahman, Suhaimi (Penerbit Universiti Kebangsaan Malaysia, 2015)
This study discusses the importance of implementing E-Syariah, which is a Government-to-Citizen (G2C) application, in fulfi lling the needs to improve Shariah Courts’ administration in Malaysia. Its objective is to identify factors that affect the intention and utilization of E-Syariah by its targeted users, the Malaysian Shar’ie lawyers, which are currently lacking. A self-administered questionnaire was utilized and responses from 240 Shar’ie lawyers were collected and analyzed using structural equation modeling (SEM). Results from the analysis indicate that behavioral intention to use E-Syariah is positively infl uenced by performance expectancy and technical facilitating conditions; and use behavior of using E-Syariah is positively affected by behavioral intention to utilize E-Syariah. Findings from this study contribute to the literature on user acceptance of information system and can assist the federal agency and policy makers in evaluating the effectiveness of their efforts in implementing E-Syariah.